2018
DOI: 10.1016/j.tplants.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Control of Abiotic Stress Responses

Abstract: Alternative splicing, which generates multiple transcripts from the same gene, is an important modulator of gene expression that can increase proteome diversity and regulate mRNA levels. In plants, this post-transcriptional mechanism is markedly induced in response to environmental stress, and recent studies have identified alternative splicing events that allow rapid adjustment of the abundance and function of key stress-response components. In agreement, plant mutants defective in splicing factors are severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
364
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(374 citation statements)
references
References 95 publications
7
364
0
3
Order By: Relevance
“…The isoforms and altered proteins arising from alternative splicing are indeed known to potentially assist in stress tolerance (Kamies, Farrant, Tadele, Cannarozzi, & Rafudeen, 2017). Although the role and importance of adjustments in splicing pattern although established at transcript level (Ding et al, 2014;Laloum, Martín, & Duque, 2017;Syed, Kalyna, Marquez, Barta, & Brown, 2012), proteomic validations of phosphorylation-mediated regulation of splicing machinery remain elusive.…”
mentioning
confidence: 99%
“…The isoforms and altered proteins arising from alternative splicing are indeed known to potentially assist in stress tolerance (Kamies, Farrant, Tadele, Cannarozzi, & Rafudeen, 2017). Although the role and importance of adjustments in splicing pattern although established at transcript level (Ding et al, 2014;Laloum, Martín, & Duque, 2017;Syed, Kalyna, Marquez, Barta, & Brown, 2012), proteomic validations of phosphorylation-mediated regulation of splicing machinery remain elusive.…”
mentioning
confidence: 99%
“…Research showed that AS can adjust the function of important plant stress-response components [84,85]. In order to response to the invasion or attack from pathogens and pests, plant evolved defense mechanisms which involve multiple signal cascades and protein networks to provide specific and comprehensive defenses.…”
Section: As Events Related To Pawb Response In P Fortuneimentioning
confidence: 99%
“…Alternative splicing (AS) is another regulatory level that has been detected in plants under salinity. More than 2000 AS events have been reported for salinity-treated plants (Ding et al 2014;Laloum et al 2017). Other regulatory levels reported under salinity include epigenetic modifications (Chinnusamy & Zhu 2009;Dhar et al 2014;Guangyuan et al 2007;Labra et al 2004) and miRNAs (Jian et al 2016;Noman et al 2017;Stief et al 2014;Zhang 2015).…”
Section: Overview Of Plant Salt-responsive Molecular Mechanismsmentioning
confidence: 99%